Caracterización física -química del edulcorante sólido obtenido a partir de la Jícama (Pachyrhizus erosus) - Yépez Gavi, Remigio David (2016)
This investigation has as purpose to give value I attack to the jicama, because this ancestral tuber is in extinction danger, he/she has nutritional components that can be part of the daily diet for those people that cannot consume high products in colorines. He/she was carried out a process diagram for the obtaining of the sweetener been accustomed to starting from the jicama. Realized studies on the jicama have determined that they have big nutritional contributions and the main characteristic is in their you sugar, where he/she stands out the high content of Fructooligosacaridos (FOS) in its juice for the obtaining of the accustomed to sweetener was developed the following stages: it harvests (7 months), laundry, extraction of the juice, in which lemon juice was used to avoid the enzymatic pardeamiento, later on underwent cooking for its concentration eliminating the content of evaporative water in the one which, as the concentration of the solution is increased expressed in grades brix, the boiling point is also increased. That is to say the increment of the boiling point is directly proportional to the concentration of the solution; they were carried out several rehearsals, once selected the best formulation the analysis of the sweetener was made been accustomed to in which we determine the main hydrates carbon like Sucrose, Fructose, Inulin, and Glucose. .